Stała stymulacja serca u dzieci - wskazania, techniki implantacji oraz powikłania - Polewczyk, Aneta Maria; Polewczyk, Maciej; Kutarski, Andrzej; Polewczyk, Anna (Pediatria Polska - Polish Journal of Paediatrics, 2017)
The electrotherapy in pediatric patients dates from the early 60s of the twentieth cen-tury. Cardiac conduction abnormalities and arrhythmias may be associated with inflammation, congenital heart disease, cardiac surgery in the past, and autoimmune disease in mother (antibodies SS-A, SS-B). In past years, electrodes haye been implanted epicardial manner, almost exclusiyely. Nowadays, this method is rather preferred in the youngest children with slight body size, complicated cardiac deformities, right-to-left intracardiac shunting or in the post-operatiye absence of yenous access to the right heart. Increasing number of transyenous implantations is performed because of technological progress, miniaturizaion and more adyanced operator experience. Howeyer, deyelopment of the young organism, intensiye physical actiyity of the children and sometimes impro-per implantation technique may lead to serious complications. In our article we would like to summarize the present knowledge of indications, implantation techniques and complications management of electrotherapy in children